THE INFLUENCES OF CAREER GUIDANCE ON THE ACCURACY OF CHOOSING VOCATIONAL SCHOOLS DEPARTEMENT - Patrick Pangkey; Meisie L Mangantes (Prodi Bimbingan Konseling Universitas Negeri Manado, 2020)
Future planning needs to be implemented from an early age. Lack of career guidance leads to a lack of career information for students, which affects student career decisions. The purpose of this study was to determine the relationship between career guidance and the accuracy of choosing a vocational school student major. This type of research was experimental. The study population was 80 Vocational High School students. From the results of the study, it was known that career guidance influenced the accuracy of choosing a vocational school student major. This was dominated by the finding that each student was able to choose a major according to their talents and interests.